Congenital Peritoniopericardial Diaphragmatic Hernia in a Female Kitten - Camargo, Karine; Eduardo Alberto Tudury; Grazielle Anahy de Sousa Aleixo Cavalcanti; Robério Silveira de Siqueira Filho; Luana Mirela de Sales Pontes; Joana Luiza Crispiniano Cunha Santos; Maria Raquel de Almeida; Levi Auto Lopes (Acta Scientiae Veterinariae, 2023)
Background: Peritoneopericardial diaphragmatic hernia is a rare pathogenesis of congenital origin, which occurs due to a failure in the communication between the diaphragm and the pericardium during embryogenesis. Symptoms may be non-existent or non-specific, depending on the herniated organ involved and, in most cases, the diagnosis is incidental. Regarding the most indicated treatment, there are still divergences in the literature concerning the indication of conservative or surgical treatment. This study reports the case of a feline peritoneopericardial hernia, for which surgical correction was the treatment of choice. Case: A 3-month-old female kitten, no defined racial pattern, was referred to the Veterinary Hospital of the Federal Rural University of Pernambuco for treatment of a peritoneopericardial diaphragmatic hernia. This condition was diagnosed through radiographic examination after the patient having been submitted to pediatric castration and presented anesthetic complications in the transsurgery. Blood count, biochemical profile and Doppler echocardiogram were performed, which showed no significant changes. To obtain a better study and surgical planning, computed tomography was performed to observe the heart located cranially in the pericardial cavity. Caudally to the heart, hepatic parenchyma located in the pericardial cavity was observed; and hepatic vessels presenting slightly enlarged dimensions. These tomographic findings suggested peritoneopericardial diaphragmatic hernia; being the liver present in the pericardial cavity and signs of congestion in the hepatic parenchyma. Due to the likelihood of future worsening of the hernia, surgical correction was performed, with an abdominal midline incision in the preumbilical region to reposition the liver to its normal anatomy, followed by diaphragm reconstitution through a herniorrhaphy. After the surgical procedure, the patient was referred for observation in internment and, after 15 days, the skin sutures were removed. Complete correction of the hernial defect was observed on radiography performed 30 days after the surgical procedure. However, the examination showed the presence of deviation/deformity in the topography of the sternum and costal cartilages, with slight cardiac displacement to the right hemithorax, suggesting the presence of pectus excavatum. Discussion: Peritoneopericardial diaphragmatic hernia is considered rare and, despite being one of the most common causes of congenital pericardial anomaly in felines, it has a low prevalence ranging from 0.06% to 1.45%. They are usually diagnosed from two years of age, with prevalence for older animals. However, due to having presented anesthetic changes, the patient of this case report could be diagnosed early. Among the most common organs that migrate to the thoracic cavity, the liver is the most commonly observed, which is also the hernia content of the present report. Peritoneopericardial hernia is often diagnosed through radiography and ultrasound, and these imaging tests proved to be sufficient for the diagnosis in this report. However, computed tomography was important for providing a better study of case and for the adoption of median celiotomy as a treatment. Associations with other malformations are described in the literature, with pectus excavatum being the most common and also observed in this report. Peritoneopericardial diaphragmatic hernia is a rare anomaly, rarely reported in the literature and with divergences regarding its treatment. The adoption of early surgical treatment performed in this report showed satisfactory evolution and the possibility of a favorable prognosis. Keywords: congenital anomaly, celiotomy, congenital diaphragmatic hernia. Descritores: anomalia congênita, celiotomia, hérnia diafragmática congênita.